The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/mbc.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Is the time in therapeutic range using the ratio of tests equivalent to the Rosendaal method?

Abstract: The percentage of time in therapeutic range (TTR) is a measure of anticoagulation quality with vitamin K antagonists (VKAs). The method most commonly used in clinical trials is the Rosendaal TTR. However, the application of this method in daily practice for clinical decision lacks appropriate instruments. We aimed to evaluate the percentage of tests within the target international normalized ratio (INR) (tests ratio) as a surrogate of Rosendaal TTR. We performed an observational and retrospective study to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…The study was a retrospective analysis of 633 patients managed by a university hospital‐based, pharmacist‐managed anticoagulation clinic in the USA, with 1 year of follow‐up. Recently, a retrospective cohort study of 377 VKA‐treated outpatients attending the cardiology anticoagulation clinic of a Portuguese hospital showed that FIR and TTR were significantly correlated but not equivalent, due to high variability between the parameters (Caldeira et al , ). Our study extends these findings by analysing data from an international cohort of 8445 prospective patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study was a retrospective analysis of 633 patients managed by a university hospital‐based, pharmacist‐managed anticoagulation clinic in the USA, with 1 year of follow‐up. Recently, a retrospective cohort study of 377 VKA‐treated outpatients attending the cardiology anticoagulation clinic of a Portuguese hospital showed that FIR and TTR were significantly correlated but not equivalent, due to high variability between the parameters (Caldeira et al , ). Our study extends these findings by analysing data from an international cohort of 8445 prospective patients.…”
Section: Discussionmentioning
confidence: 99%
“…Se calculó el TRT mediante el método de Rosendaal (18,19,20), considerándose como control óptimo TRT ≥60% y control subóptimo TRT <60%. Este es el valor utilizado en los estudios clínicos internacionales (19,20).…”
Section: Procedimiento Y Técnicasunclassified
“…Se calculó el TRT mediante el método de Rosendaal (18,19,20), considerándose como control óptimo TRT ≥60% y control subóptimo TRT <60%. Este es el valor utilizado en los estudios clínicos internacionales (19,20). Los grupos fueron sometidos a análisis para determinar la asociación con los factores edad, género, grado de instrucción, dependencia funcional, deterioro cognitivo, comorbilidades, discontinuidad terapéutica y polifarmacia, así como el porcentaje de ACV y sangrado en ambos grupos.…”
Section: Procedimiento Y Técnicasunclassified
See 2 more Smart Citations